Macroscopic assembled graphene nanofilms based room temperature ultrafast mid‐infrared photodetectors. Issue 6 (18th March 2022) - Peng, Li; Liu, Lixiang; Du, Sichao; Bodepudi, Srikrishna Chanakya; Li, Lingfei; Liu, Wei; Lai, Runchen; Cao, Xiaoxue; Fang, Wenzhang; Liu, Yingjun; Liu, Xinyu; Lv, Jianhang; et al.
Abstract: Graphene with linear energy dispersion and weak electron–phonon interaction is highly anticipated to harvest hot electrons in a broad wavelength range. However, the limited absorption and serious backscattering of hot‐electrons result in inadequate quantum yields, especially in the mid‐infrared range. Here, we report a macroscopic assembled graphene (nMAG) nanofilm/silicon heterojunction for ultrafast mid‐infrared photodetection. The assembled Schottky diode works in 1.5–4.0 μm at room temperature with fast response (20–30 ns, rising time, 4 mm 2 window) and high detectivity (1.6 × 10 11 to 1.9 × 10 9 Jones from 1.5 to 4.0 μm) under the pulsed laser, outperforming single‐layer‐graphene/silicon photodetectors by 2–8 orders. These performances are attributed to the greatly enhanced photo‐thermionic effect of electrons in nMAG due to its high light absorption (~40%), long carrier relaxation time (~20 ps), low work function (4.52 eV), and suppressed carrier number fluctuation. The nMAG provides a long‐range platform to understand the hot‐carrier dynamics in bulk 2D materials, leading to broadband and ultrafast MIR active imaging devices at room temperature. Abstract : Graphene with linear energy dispersion and weak electron–phonon interaction is highly anticipated to harvest hot electrons in a broad wavelength range. However, the limited absorption and serious back scattering of hot‐electrons result in inadequate quantum yields, especially in the mid‐infrared range. Here, the greatly enhanced photo‐thermionic effect of wafer‐scale macroscopic assembled graphene nanofilm largely extends the photodetection of graphene/silicon Schottky diode from 1.5 to 4 μm.